Praxeological analysis of measures of central tendency in grade VIII mathematics textbooks: Identifying learning obstacles and improving task presentation - Dewi, Rivani Adistia; Harahap, Putri Ardhanita; Juandi, Dadang; Turmudi, Turmudi (Universitas Islam Negeri Raden Intan Lampung, 2026)
Students continue to experience difficulties understanding measures of central tendency, and the way statistical tasks are presented in textbooks may contribute to these difficulties. However, studies examining textbook task presentation from a praxeological perspective remain limited. This study aims to analyze the presentation of measures of central tendency in Grade VIII mathematics textbooks using a praxeological framework and to propose improvements to minimize students' learning obstacles. This study employed a qualitative, praxeological approach to examine the textbook's task presentation. The findings indicate that several tasks have the potential to generate ontogenic, didactic, and epistemological obstacles, arising from the absence of prior conceptual explanations, inaccuracies in visual representations, and insufficient connections between different forms of data representation, which may limit students’ conceptual understanding and encourage procedural reasoning. These findings imply that teachers need to provide additional conceptual support when using textbooks. In contrast, textbook authors and curriculum developers should design tasks that are conceptually structured, use accurate representations, and include gradual transitions between different forms of data to better support students' understanding.